Research on Satellite Power System Based on MPPT Technology - Wenshuang ZHANG; Wentao YU; Qiang WEI (天地一体化信息网络)
According to the need of power system for GEO satellite,the plan design and simulation based on Maximum Power Point Tracking (MPPT) technology were designed and simulated.It could reduce the power loss in power transport line and made full use of the output power of solar array.Based on the research and simulation for solar array,the simulation of all the power system was fi nished.The result of simulation provides that it can complete the MPPT function and stabilize the bus voltage.Last,the new plan and the traditional one were compared,which shows the advantage of the new plan and lays a foundation for next power system.